Persepsi Diri dan Pola Pikiran Individu yang Mengalami Anxiety Kronis - Ulfa Laila Nazirah; Sri Nurhayati Selian (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to explore self-perception and thought patterns among university students experiencing chronic anxiety using a qualitative descriptive approach. Data were collected from three students aged 18-25 through in-depth interviews and observation, analyzed via Miles and Huberman's interactive model. Findings reveal that chronic anxiety is triggered by fear of failure, past trauma, and social comparison, manifesting in somatic symptoms like heart palpitations and stomach issues. Negative self-perception (self-discrepancy) and catastrophic thinking (overthinking, intolerance of uncertainty) perpetuate the anxiety cycle, while spiritual coping such as prayer offers temporary relief. The conclusion highlights the need for professional interventions to enhance resilience and support in academic settings.